The Legal Position Of Multinational Corporation In International Law - Rinwigati, Patricia (UI Scholars Hub, 2019)
It has been recognised that Multinational Corporation has played important role in international law particularly on economic matters and recently on human rights. Hence, the question is how international law views this entity: is it a subject or object of international law? What kind of modalities and limitations for MNC to operate in international law? Do they have some capacities for law making treaty? This article attempts to answer those questions critically by Public International Law as a point of departure. It is argued here that different theories used lead to different conclusion on the position of multinational corporation in International Law. Nevertheless, such differences will not delete the fact that this entity has certain rights and obligations in International Law.